2013
DOI: 10.1038/onc.2013.323
|View full text |Cite
|
Sign up to set email alerts
|

The telomere profile distinguishes two classes of genetically distinct cutaneous squamous cell carcinomas

Abstract: The incidence of skin cancer is increasing worldwide and cutaneous squamous cell carcinomas (SCCs) are associated with considerable morbidity and mortality, particularly in immunosuppressed individuals ('carcinomatous catastrophy'). Yet, molecular mechanisms are still insufficiently understood. Besides ultraviolet (UV)-indicative mutations, chromosomal aberrations are prominent. As telomeres are essential in preserving chromosome integrity, and telomere erosion as well as aberrant spatial telomere distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…A PDT-stressed cell that expresses telomerase could lead to SCC development. Indeed, it has been shown that telomeres play an important role in skin carcinogenesis (23).…”
Section: Resultsmentioning
confidence: 99%
“…A PDT-stressed cell that expresses telomerase could lead to SCC development. Indeed, it has been shown that telomeres play an important role in skin carcinogenesis (23).…”
Section: Resultsmentioning
confidence: 99%
“…SCC development is a multistep process leading to highly complex karyotypes with large cytogenetic heterogeneity . Besides mutational inactivation of Cellular tumor antigen p53, additional aberrations, such as amplification of chromosome 11q13/cyclin D1 or loss of chromosome 15/thrombospondin 1, are known to modulate the cell or its environment .…”
mentioning
confidence: 99%
“…Intraspecies investigations have shown the intricacy of telomere biology: for example telomere length is uneven within individuals and tissues (Leufke et al 2014); telomerase activity is tissue context sensitive (Krunic et al 2009) and replication is not the only mechanism of telomere attrition (von Zglinicki 2002). Notwithstanding this complexity, comparative investigations in cell culture systems have shown fundamental differences among mammals (Seluanov et al 2007; Lorenzini et al 2009; Gomes et al 2011).…”
Section: Cellular Characteristics Possibly Related To the Evolution Omentioning
confidence: 99%